2008
DOI: 10.1038/ismej.2008.28
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and functional gene analysis of the bacterial and archaeal communities associated with the surface microlayer of an estuary

Abstract: The surface microlayer (SML) is the thin biogenic film found at the surface of a water body. The SML is poorly understood but has been shown to be important in biogeochemical cycling and sea-air gas exchange. We sampled the SML of the Blyth estuary at two sites (salinities 21 and 31 psu) using 47 mm polycarbonate membranes. DNA was extracted from the SML and corresponding subsurface water (0.4 m depth) and microbial (bacteria and archaea) community analysis was performed using denaturing gradient gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 81 publications
4
56
0
2
Order By: Relevance
“…More recent evidence published in The ISME Journal supports the observations made in the North Sea by Franklin et al (2005) and shows distinct bacterioneuston communities are also present in estuarine surface microlayers (Cunliffe et al, 2008). Denaturing gradient gel electrophoresis comparison of bacterial and archaeal 16S rRNA genes from surface microlayer and subsurface water samples at two sites along the estuary showed that bacteria form distinct surface microlayer-specific community structures.…”
supporting
confidence: 67%
“…More recent evidence published in The ISME Journal supports the observations made in the North Sea by Franklin et al (2005) and shows distinct bacterioneuston communities are also present in estuarine surface microlayers (Cunliffe et al, 2008). Denaturing gradient gel electrophoresis comparison of bacterial and archaeal 16S rRNA genes from surface microlayer and subsurface water samples at two sites along the estuary showed that bacteria form distinct surface microlayer-specific community structures.…”
supporting
confidence: 67%
“…King (2003) made a wider PCR-based survey of coxL genes across strains from two phyla (Proteobacteria and Actinobacteria) and also showed monophyletic groupings similar to 16S rRNA gene phylogeny. The concordance of coxL gene and 16S rRNA gene phylogeny has significant practical implications if coxL genes are used as molecular markers instead of 16S rRNA genes to study CO oxidiser assemblage structure in situ King, 2004, 2005;Cunliffe et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial community present in the surface microlayer is known as the bacterioneuston and has a different community structure compared with that of subsurface water below (Cunliffe et al, 2008, 2009a, Franklin et al, 2005. Monitoring of the bacterioneuston community structure during a fjord mesocosm experiment, using Bacteria 16S rRNA gene terminal restriction fragment length polymorphism and denaturing gradient gel electrophoresis (DGGE), showed distinct and consistent differences between the bacterioneuston and the bacterioplankton communities (Cunliffe et al, 2009c).…”
mentioning
confidence: 99%
“…Community samples were collected from the surface microlayer using a metal mesh screen (Garrett Screen; 16 mesh stainless steel screen, size 275 Â 275 mm, sampling depth 0 to 400 mm) and subsurface water (sampling depth 0.75 m). For each sample, 250 ml of water was filtered using a Sterivex-GS filter unit (pore size 0.2 mm; Millipore, Watford, UK) and DNA was extracted from the filter in a sucrose buffer using lysozyme, proteinase K, sodium dodecyl sulphate and phenol-chloroform (Cunliffe et al, 2008). The re-suspended DNA was diluted in molecular grade water to a concentration of 30 ng ml À1 and stored at À20 1C.…”
mentioning
confidence: 99%